The effect of beet juice (beta vulgaris) to increase hemoblobin levels in pregnant women at The Kuala Tadu Health Center Tadu Raya Sub-District, Nagan Raya District - Damayanti, Siti; Satria, Orita; Zakiya, Zakiya; Ala, Nurul (Journal of Midwifery and Nursing, 2025)
Anemia is a condition where the body experiences a lack of hemoglobin levels in the blood which will cause reduced oxygen flow to the organs of the body. To find out if drinking beet juice helps pregnant women have more hemoglobin.  In this study, we used an experimental design involving testing one group of subjects before and after the intervention. A total of 32 pregnant women were sampled using total sampling technique. They were given 200 grams of beetroot juice in 250 ml/day for 7 days. Shows The statistical tests, using a paired sample t-test, showed a P value of 0.000, which is less than 0.05. This means there was a noticeable difference in hemoglobin levels before and after the treatment. These results suggest that giving beet juice greatly helps increase hemoglobin levels in pregnant women with mild to moderate anemia. It can be concluded that the administration of beet juice can be made a reference as an intervention for pregnant women who experience problems with anemia or lack of hemoglobin levels in the blood from mild to moderate categories. The researcher hopes that the health center can increase its role in supporting pregnant women in treatment and how to prevent or handle the occurrence of anemia during pregnancy by increasing the mother's knowledge related to the handling and prevention of anemia by utilizing plants and other alternatives that are cheap and easy to obtain.